Integration of Educational Technology: Enhancing Prose and Poetry Creativity Through Digital Media in Elementary Schools - Shintarahayu, Balqis (Assyfa Learning Journal, 2025)
Technology integration in the Indonesian Language curriculum in elementary schools is becoming increasingly important in today's digital era. This study examines the use of creative applications and digital platforms to enrich prose and poetry learning for grade 5 students. With a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, we developed a web-based learning media called "SastraOnline" and interactive software such as "PuisiKreatif" to enhance student creativity and engagement. This study collected longitudinal data from 10 elementary schools to identify patterns of 5th-grade students' engagement and creativity in technology-based learning. Results showed a significant increase in student engagement by 25% and self-expression skills by 20%. However, variations in implementation across schools affected the results, indicating the importance of local curriculum adaptation. To address the challenges of teacher training, we propose a continuous training program tailored to schools' needs. Collaboration between schools, government, and technology providers is proposed to facilitate the development of a dynamic and responsive curriculum. Further research is needed to measure long-term impacts and tailor effective implementation strategies across educational contexts.